A semiempirical quantum chemistry approach to possible structures and energies of hydrogen atoms adsorbed on Pt(100) and Pt(111) clusters at a simulated Pt/aqueous electrochemical interface - Zinola Sánchez, Carlos Fernando (1996)
Extended Hueckel molecular orbital calculations for the adsorption of H-atoms in a simulated aqueous electrochemical environment on Pt(111) and Pt(100) clusters were made. Different adsorbate configurations were considered. H-atom adsorption on hollow sites coadsorbed with an on top OH-species for Pt(111), and H-atom adsorption on bridge sites for Pt(100) are favoured. At potentials lower than the hydrogen electrode equilibrium potential, H-adatom configurations involving subsurface Pt atoms can also be formed. For both Pt(111) and Pt(100), these structures are probably related to species involved in the H-atom electrosorption and hydrogen evolution reaction.